Climate Resilient Options for Management of Maize Diseases in India - S.S. SHARMA, ROBIN GOGOI, HARLEEN KAUR, N. MALLIKARJUNA, R.K. DEVLASH, A. BASANDRAI, K.S. HOODA*, M.K. KHOKHAR, JYOTI KAUL, CHIKKAPPA G. KARJAGI, BHUPENDER KUMAR; S.K. SINGH, PRADEEP KUMAR, I.K. KALPPANAVAR and PRAVASINI BEHERA, C. CHANDRASHEKARA, VINOD KUMAR (Indian Phytopathology, 2016)
Maize (Zea mays L.) is the third most important crop of country after rice and wheat and is cultivated round the year. Diseases are one of the major constraints in realizing its potential yield particularly under changing climate scenario. Therefore, attempts were made to identify promising components suitable for the management of major maize diseases through conducting multi-environment field experiments at 12 locations (Bajaura,Ludhiana,Karnal,Delhi,Pantnagar,Dhaulakuan, Bhubaneswar,Godhra, Almora, Arbhavi, Udaipur and Mandya) during Kharif 2014. The results showed that trifloxystrobin 25% + tebuconazole 50% (0.05%) and validamycin (0.1%) were effective in containing banded leaf and sheath blight (50.69% and 43.27% control respectively) across locations except Almora where seed treatment (ST) of T. viride + foliar sprays (FS) of validamycin (0.1%) was significantly superior (65.0% control) over other treatments. On the other hand, tebuconazole (0.5%) was significantly superior (38.4% disease control) in the management of turcicum leaf blight whereas azoxystrobin (0.05%) was effective in management of common rust (53.8% control). Seed treatment with Rauvolfia serpentina leaves (0.5 ml extract /liter water) and foliar spray of carbendazim 12 WP + mancozeb 63 WP @ 0.3% significantly reduced maydis leaf blight (40.7% control). The combination of propiconazole + mancozeb ST (1:1) @ 4 g/kg ST + FS (0.25%) prior to flowering provided significant control of charcoal rot and fusarium stalk rot (35.6 & 65.4% control respectively). Seed treatment with metalaxyl + mancozeb (1:1) @ 0.25% followed by its use as foliar sprays (0.25%) was highly effective in managing sorghum downy mildew with 92.5% control. Climate resilient disease management options identified in the study can help maize growers in safeguarding the crop from diseases in different ecologies of India.